Problem Based Learning (PBL) Assisted Virtual Laboratory: Effects on Improving Learning Motivation and Science Process Skills of Electricity for Vocational High School Students - Ranti, Linda; Yennita, Y; Irawan, Dedi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to increase students' motivation to learn physics through the application of the Problem Based Learning learning model. This research is considered very important because the results of the analysis of students' initial abilities through teacher and student respondents give low results. This research is a class action research (PTK) conducted in two cycles. The material in the first cycle is static electricity and dynamic electricity while the material in the second cycle is electromagnetic field. This research was conducted at SMKN 1 Tambang in Kampar Regency, Riau Province, with 19 students in class X of Machining Engineering, 16 males and 3 females. The steps in this PTK start from the pre-cycle stage (initial ability analysis), making learning tools and instruments, validating devices and instruments, taking action, evaluation, and reflection. The assessment of students' learning motivation and science process skills was carried out after the cycle ended which was assessed by the teacher himself through a learning motivation questionnaire totaling 35 items and student science process skills questions with a total of 18 multiple-choice questions. The average percentage of students' motivation to learn physics for cycle 1 was 68.30% in the medium category and in cycle 2 was 73.98% in the high category. Meanwhile, for the science process skills test, students in cycle 1 obtained results of 57.02% of the category were quite good and in cycle II, which was 77.48% of the high category. The increase in learning motivation can be seen from the change in the percentage of learning motivation questionnaires from the medium category to high and the change in science process skills can be seen from the change in test results from the fairly good category to good.Keywords: problem based learning learning model, learning media, learning motivation, science process skills